Lessons learnt from the implementation of a colorectal cancer screening programme for lynch syndrome in a tertiary public hospital. (February 2023) - Dueñas, Nuria; Navarro, Matilde; Sanjuán, Xavier; Ruiz, Núria; Iglesias, Silvia; Matias-Guiu, Xavier; Guardiola, Jordi; Kreisler, Esther; Biondo, Sebastiano; González, Sara; Legido, Raquel; Blanco, Ana; et al.
Abstract: Background: Lynch syndrome (LS) is the first cause of inherited colorectal cancer (CRC), being responsible for 2–4% of all diagnoses. Identification of affected individuals is important as they have an increased lifetime risk of multiple CRC and other neoplasms, however, LS is consistently underdiagnosed at the population level. We aimed to evaluate the yield of LS screening in CRC in a single-referral centre and to identify the barriers to its effective implementation. Methods: LS screening programme included individuals with CRC < 70 years, multiple CRC, or endometrial cancer at any age. Mismatch repair (MMR) protein immunohistochemistry (IHC) analysis was performed in routine practice on the surgical specimen and, if MLH1 IHC was altered, MLH1 gene promoter methylation was analysed. Results were collected in the CRC multidisciplinary board database. LS suspected individuals (altered MMR IHC without MLH1 promoter methylation) were referred to the Cancer Genetic Counselling Unit (CGCU). If accepted, a genetic study was performed. Two checkpoints were included: review of the pathology data and verification of patient referral by a genetic counsellor. Results: Between 2016 and 2019, 381 individuals were included. MMR IHC analysis was performed in 374/381 (98.2 %) CRC cases and MLH1 promoter methylation in 18/21 (85.7 %). Seventeen of the 20 LS suspected individuals were invited for referral at the CGCU. Two cases were not invited and the remaining patient died of cancer before completion of tumour screening. Fifteen individuals attended and a genetic analysis was performed in 15/20 (75 %) LS suspected individuals. Ten individuals were diagnosed with LS, in concordance with the IHC profile (2.7 % of the total cohort). This led to cascade testing in 58/75 (77.3 %) of the available adult relatives at risk, identifying 26 individuals with LS. Conclusions: Establishing a standardized institutional LS screening programme with checkpoints in the workflow is key to increasing the yield of LS identification. Highlights: Establishing a Lynch syndrome CRC screening programme is key to identify Lynch syndrome individuals. Checkpoints limit patient loss. The workflow is easy to follow.